2012
DOI: 10.1017/s0031182012001254
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of phosphoenolpyruvate carboxykinase fromRaillietina echinobothrida, a cestode parasite of the domestic fowl

Abstract: Phosphoenolpyruvate carboxykinase (PEPCK, EC 4.1.1.32) is an essential regulatory enzyme of glycolysis in helminths in contrast to its role in gluconeogenesis in their host. Previously we have reported that phytochemicals from Flemingia vestita (Family: Fabaceae), genistein in particular, have vermifugal action and are known to affect carbohydrate metabolism in the cestode, Raillietina echinobothrida. In order to determine the functional differences of PEPCK from the parasite and its avian host (Gallus domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In this line of evidence, we showed that Met induces a decrease in glycogen levels, the major energy reserve in parasite tissue, and an increase in Eg-α-amylase and Eg-LDH activities, indicating an increase in these catabolic processes in Echinococcus larval stages (Fig 2A and 2B ). On the other hand, our results also showed a decreased expression of Eg- pepck , which encodes a CO 2 -fixing enzyme that participates in the glycolytic pathway of parasitic helminthes [ 30 , 60 , 61 ], and Eg-MDHc, a critical enzyme in the malate—aspartate conversion, both key enzymes in the intermediary metabolism of cestodes [ 30 , 62 ]. This could be affecting the generation of cytosolic and mitochondrial NADH/NAD + , further compromising the ATP pools in Echinococcus Met-treated cells and causing metabolic exhaustion in the parasite.…”
Section: Discussionmentioning
confidence: 92%
“…In this line of evidence, we showed that Met induces a decrease in glycogen levels, the major energy reserve in parasite tissue, and an increase in Eg-α-amylase and Eg-LDH activities, indicating an increase in these catabolic processes in Echinococcus larval stages (Fig 2A and 2B ). On the other hand, our results also showed a decreased expression of Eg- pepck , which encodes a CO 2 -fixing enzyme that participates in the glycolytic pathway of parasitic helminthes [ 30 , 60 , 61 ], and Eg-MDHc, a critical enzyme in the malate—aspartate conversion, both key enzymes in the intermediary metabolism of cestodes [ 30 , 62 ]. This could be affecting the generation of cytosolic and mitochondrial NADH/NAD + , further compromising the ATP pools in Echinococcus Met-treated cells and causing metabolic exhaustion in the parasite.…”
Section: Discussionmentioning
confidence: 92%
“…This research suggested that tetrahydropalmatine (1) disturbs the downstream signalling pathway of NO, as shown by the change in cGMP concentration in the tissues of R. echinobothrida (Das et al 2009). A further study by the same group (Das et al 2013) found that 1 together with other alkaloids inhibits the activity of phosphoenolpyruvate carboxykinase, an important regulatory enzyme of glycolysis in R. echinobothrida in contrast to its role in gluconeogenesis in their host, domestic fowl. An aqueous extract from the rhizomes of S. glabra and its equimolar mixture with root extract of T. multiloba Miq.…”
Section: Anthelmintic Activitymentioning
confidence: 96%
“…The enzyme from the cestode Raillietina echinobothrida is activated by a variety of plant extracts [200].…”
Section: Other Metabolic Pathwaysmentioning
confidence: 99%